2021
DOI: 10.1111/hsc.13674
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with perceptions of dignity and well‐being among older people living in residential care facilities in Sweden. A national cross‐sectional study

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…As in the present study, poor-rated health and dementia were important factors. A cross-sectional study focusing on RCF found similar results [ 46 ]. Considering the aforementioned findings in the pre-pandemic period, the findings of the present study on the impact of disrespect by staff on feelings of loneliness and anxiety during the pandemic are not surprising.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…As in the present study, poor-rated health and dementia were important factors. A cross-sectional study focusing on RCF found similar results [ 46 ]. Considering the aforementioned findings in the pre-pandemic period, the findings of the present study on the impact of disrespect by staff on feelings of loneliness and anxiety during the pandemic are not surprising.…”
Section: Discussionmentioning
confidence: 55%
“…As in the present study, poor-rated health and dementia were important factors. A cross-sectional study focusing on RCF found similar results [46]. Considering the…”
Section: Discussionmentioning
confidence: 68%
“…27 In addition to constructs in the framework of person-centered practice, previous authors have found significant associations between self-rated health, mobility, and dementia and perceptions of dignity and well-being. [28][29][30] Using a modified Delphi process to prioritize essential 'dignity-conserving care markers', Thompson and colleagues 17 found the following practices to be good markers: staff make residents feel valued as a person; staff are compassionate in providing care; residents can trust staff; staff do not make residents feel like a burden to others; residents are able to make choices in their everyday life; 17 assistance with hygiene and personal matters is adequate and sensitive; there is freedom to complain without fear of repercussions; staff does not talk about residents in front of other residents; the personal space of the residents and the need for privacy are respected; efforts are made to make residents feel safe.…”
Section: Threats To Dignity In Ltc Homesmentioning
confidence: 99%
“…26 In addition to constructs in the framework of person-centered practice, previous authors have found significant associations between self-rated health, mobility, and dementia and perceptions of dignity and well-being. [27][28][29] Using a modified Delphi process to prioritize essential 'dignity-conserving care markers', Thompson and colleagues 17 found the following practices to be good markers: staff make residents feel valued as a person; staff are compassionate in providing care; residents can trust staff; staff do not make residents feel like a burden to others; residents are able to make choices in their everyday life; 17 assistance with hygiene and personal matters is adequate and sensitive; there is freedom to complain without fear of repercussions; staff does not talk about residents in front of other residents; the personal space of the residents and the need for privacy are respected; efforts are made to make residents feel safe.…”
Section: Threats To Dignity In Ltc Homesmentioning
confidence: 99%
“…This approach targets the attitudes of staff and the care environment, which could be used when designing interventions to promote dignity and well-being. 27 In conclusion, dignity in the LTC goes through the recognition of its need and the support of public policies that, in addition to monitoring, promote more significant knowledge about the reality of the care offered. This also means the confrontation of prejudice about this service model 27 and the urgent creation of strategies for designing and implementing sustainable and equitable LTC systems 28 that ensure a person-centered service with dignity to everyone who needs it.…”
Section: Threats To Dignity In Ltc Homesmentioning
confidence: 99%